Homosexuality and Psychoanalytic Training: Struggles in England and North America - What Implications for South Africa? - Kottler, Amanda (PINS-Psychology in Society, 2026)
In May 1995 a Letter of Concern (LOC), signed by 180 psychotherapists (Appendix A), with a covering letter from Andrew Samuels (1995a), a training analyst of the Society of Analytical Psychology, was sent to The Secretary of State for Health in Britain. The LOC expressed concern about issues related to negative and defensive attitudes towards training homosexuals as psychotherapists I obtained a copy of this correspondence whilst visiting in July 1995. Later that year, In October 1995, at an International Psychoanalytic Association conference in America, I overheard a discussion between a senior training and supervising analyst at an extremely prestigious Institute for Psychoanalysis (Dr T), and a Clinical Faculty member of the Department of Psychiatry at the University of California (Sharone Abramowitz), in which the latter refused again, an invitation to train as an analyst. This was because of the negative attitude towards homosexuality held by training analysts These circumstances, together with Young’s interesting and provocative article "Is ’perversion’ obsolete?" (PINS 21, 1996) have prompted me to report something of their content. My aim is to generate discussion leading to some theorising around concrete issues of the well known, though covert, widespread exclusion of homosexuals from psychoanalytic training. Given that this topic, as far as I know, has never been raised for public debate in South Africa, it seems timely to draw attention to it now, particularly since we are the first country in the world which has a constitutional clause prohibiting discrimination of any sort on the basis of a person’s identification as a lesbian or a gay man. I will first cover the discussion I overheard between Dr T and Sharone Abramowitz who, together with Betsy Kaskoft (a psychotherapist in San Francisco) presented at a workshop entitled "The self and orientation: New perspectives on psychoanalysis and homosexuality: Female homosexuality, presentation and response" at the 18th Annual Conference on the Psychology of the Self - Crosscurrents in Self Psychology, held in San Francisco (ironically the so-called gay capital of the world) in October last year. I will then summarise the documents (quoting extensively from them) which I obtained In England, adding academic weight to some of the comments by referring to other literature in the field.